1999
DOI: 10.1165/ajrcmb.21.3.3467
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-5 Downregulates Tumor Necrosis Factor (TNF)–Induced Eotaxin Messenger RNA (mRNA) Expression in Eosinophils

Abstract: An eotaxin is a chemoattractant specific for eosinophils that are known to play a role in helminth infection and allergic responses. Although several cellular sources have been reported to produce eotaxin, it would be interesting to know whether eosinophils are able to produce their own eotaxin and participate in recruitment of themselves in response to inflammation. To this end, a cloned eotaxin complementary DNA was transcribed in vitro to use as a probe for detecting eotaxin messenger RNA (mRNA), and eotaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…To confirm that the EOTϪ384AϾG allele is a determinant for eotaxin1 gene transcription, the mRNA expression levels in PBMC carrying polymorphic alleles at the EOTϪ384AϾG loci were compared after stimulation with TNF-␣ which has been known to potent stimulator for eotaxin mRNA and protein production from eosinophils (38) as well as epithelial cells (26,39). Asthmatics having the homozygotic wild alleles (Ϫ384AϾG AA) showed significantly higher mRNA expression after stimulation with TNF-␣ than those having the minor allele homozygote (Ϫ384AϾG GG) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that the EOTϪ384AϾG allele is a determinant for eotaxin1 gene transcription, the mRNA expression levels in PBMC carrying polymorphic alleles at the EOTϪ384AϾG loci were compared after stimulation with TNF-␣ which has been known to potent stimulator for eotaxin mRNA and protein production from eosinophils (38) as well as epithelial cells (26,39). Asthmatics having the homozygotic wild alleles (Ϫ384AϾG AA) showed significantly higher mRNA expression after stimulation with TNF-␣ than those having the minor allele homozygote (Ϫ384AϾG GG) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2) suggests the possibility that IL-5 and eotaxin are produced by the same cells or that they mutually stimulate their production. However, eotaxin is expressed constitutively in epithelial and endothelial cells, and on macrophages, T cells and eosinophils upon activation [16, 31], whereas IL-5 is synthesized primarily by activated Th2 lymphocytes and mast cells [10]. Therefore, it is unlikely that the same cells produce IL-5 and eotaxin.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis of sputum from patients with acute exacerbation of asthma, the number of eosinophils was found to be 5 times more than that of macrophages. Furthermore, because IL-5 is able to stimulate eosinophils to synthesize eotaxin in vitro [31], eosinophil-derived eotaxin can provide an important autocrine pathway for the accumulation of eosinophils in cases of acute exacerbation. However, the rate of eotaxin expression on eosinophils was much lower than that on macrophages, regardless of the asthma type, in the present study (table 3) and other studies [17, 18, 21], which could decrease the possibility that eosinophils are the principal source of eotaxin.…”
Section: Discussionmentioning
confidence: 99%
“…We found that TNF and IL-6, but not IL-1β, are the cytokines that induce significant eosinophil shape change. TNF prolongs eosinophil survival and induces eosinophil eotaxin production, and enhances eosinophil recruitment by induction of endothelial cell adhesiveness [21, 22, 23]. An increased level of TNF is also found in asthmatic airways [24].…”
Section: Discussionmentioning
confidence: 99%